History Repeats Itself: Parental Involvement in Children’s Career Exploration - Levine, Kathy A.; Sutherland, Dawn (Canadian Journal of Counselling and Psychotherapy, 2012)
Parent involvement in children’s education remains one of the most significant predictors for children’s academic achievement. This finding generally holds across the range of social group categories including race, culture, class, and family structure. However, relatively little research has been conducted on parental involvement in children’s career exploration, specifically, the relationship between parents’ own career exploration experiences and their approach to career education with their children. Through parents and youth participating in a career development intervention program called Career Trek, the current study explored three questions: (a) How do parents perceive their roles in the children’s career development? (b) How do parents’ educational and career histories influence their perceptions of their roles? and (c) What strategies do parents utilize in terms of fostering their children’s career development needs? The parents in this study appear to perceive the facilitation of children’s career exploration as “restrictive” and therefore do not create/initiate a framework for career-related discussions. Instead, they prefer to respond when their children initiate career-related discussions. The information gained in this study is important for the facilitation of greater parental involvement in children’s career exploration. The results suggest that the best way to shift the intergenerational transmission of limited educational/career outcomes is to increase the career development exploration capacities of parents.